Робочий час як норма праці - Якушев, І.; Yakushev, І. (Східноєвропейський національний університет імені Лесі Українки, 2018)
Стаття присвячена аналізу категорії робочого часу у трудовому праві. Розкрито особливості робочого часу як тривалості виконання роботи і як режиму роботи. Розглянуто особливість тривалості робочого часу як норми виконання трудових обов’язків і як норми оплати праці. Виділено основні ознаки ненормованого робочого дня. Автор вважає за необхідне виробити єдині критерії для нормування тривалості робочого часу, протягом якого працівник зобов’язаний виконувати роботу, і за яку йому буде виплачуватися заробітна плата. Ненормований робочий день може застосовуватися лише до працівників, які виконують трудові обов’язки протягом встановленої для них норми робочого часу. The article is devoted to the analysis of the category of working time in Labor law. The Ukrainian science in the field of labor law defines working time as an obligation of an employee to perform certain work or functional duties, stipulated by an employment contract. The analysis of the norms of the Labor Code of Ukraine shows that the category of working time is used to determine the regime of work, duration of work, norms of work (measures of labor. It involves also a guarantee of labor, privileges for certain categories of workers, the duration of rest time standards, an element of social protection of workers, such as the amount of wages, the category of occupational safety and the legal provision for punishment and the protection of labor rights. This definition gives grounds to distinguish two components of the working time category in labor legislation – duration and mode of work. The article highlights the peculiar features of both components. The key findings of the study and analysis of legal norms allows to argue that there exists discrepancy between the time periods used to determine the standards of work and those to determine the rate of payment. The conclusions justify the need to establish at the legislative level identical periods for labor standards and their payment. The author proposes to stipulate in the legislation the provision that an irregular working day can be allowed only to the employees, who fully comply with their labor duties during the working time set for them.
Working Time as an Aspect of Labour Standards.
Keywords: робочий час; норма робочого часу; режим робочого часу; working time; standard of working time; working time mode